ASEAN-U.S. relations what are the talking points? - Chachavalpongpun, Pavin
This volume is the result of a workshop that had the objective to ascertain the facts of ASEAN-U.S. relations and the specific matter of the United States' engagement with ASEAN and East Asia, for possible use by ASEAN in the discussions at the next ASEAN-U.S. Summit Meeting and other ASEAN-U.S. policy forums. The book covers several elements of this relationship, ranging from U.S. military presence in the region, cooperation on maritime security, and recent U.S. policy towards Myanmar, to progress on technical cooperation.